2007
DOI: 10.1103/physreve.76.035303
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical effects and phase separation in cooled binary fluid films

Abstract: We study phase separation in thin films using the Navier-Stokes Cahn-Hilliard equations in the lubrication approximation, modeling substrate-film interactions with a van der Waals potential. We investigate the thin-film equations numerically and compare them with experimental results. We find that the model captures the qualitative features of real phase-separating fluids, in particular the tendency of concentration gradients to produce film thinning and surface roughening. The ultimate outcome of the phase se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…By promoting the constant C = νρD/ (h 0 σ 0 δ 2 ) to O (1), and by taking q > 1, this equation reduces to P = −C −1 H xx , as in Eq. (18). Similarly, the normal-stress condition reduces to νρ (∂u/∂z) h = ∂σ/∂x, which in dimensionless form reads…”
Section: After Rearrangement the Concentration Equation Becomesmentioning
confidence: 99%
See 2 more Smart Citations
“…By promoting the constant C = νρD/ (h 0 σ 0 δ 2 ) to O (1), and by taking q > 1, this equation reduces to P = −C −1 H xx , as in Eq. (18). Similarly, the normal-stress condition reduces to νρ (∂u/∂z) h = ∂σ/∂x, which in dimensionless form reads…”
Section: After Rearrangement the Concentration Equation Becomesmentioning
confidence: 99%
“…In the present case, the reduction yields two equations: one for the free surface, and one for the Cahn-Hilliard concentration. The resulting thin-film Stokes Cahn-Hilliard equations have already been introduced by the authors in [18], although the focus there was on control of phase separation and numerical simulations in three dimensions. Here we confine ourselves to the two-dimensional case: we derive the thin-film equations from first principles, present analysis of the resulting equations, and highlight the impossibility of film rupture, once a regularizing potential is prescribed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Clarke model, as it will be referred to in this chapter, utilised non-equilibrium thermodynamics based upon a free energy functional, demonstrating that phase separation generally couples to dewetting [68]: the Clarke model is explained more in section 5.1.2. A model based on the Navier-Stokes Cahn-Hilliard equations in the lubrication approximation showed that concentration gradients can create a roughened pattern that mirrors the underlying phase separation [78]. However, the film composition has no vertical dependence in these models, which means that a meaningful preferential surface attraction of blend components cannot be included.…”
Section: Models Of Deformable Fluid Filmsmentioning
confidence: 99%
“…The "Clarke model" (name introduced here) utilized nonequilibrium thermodynamics based upon a free energy functional, demonstrating that phase separation generally couples to dewetting [12]. A model based on the Navier-Stokes Cahn-Hilliard equations in the lubrication approximation showed that concentration gradients can create a roughened pattern that mirrors the underlying phase separation [14]. However, the film composition has no vertical dependence in these models, so a meaningful preferential surface attraction of blend components cannot be included.…”
mentioning
confidence: 99%